Relationship between Omega-3 Fatty Acid Intake, Nutritional Status of Third Trimester Pregnant Women and the Incidence of Low Birth Weight in Ende Regency, East Nusa Tenggara Province . - Asmulyati Saleh; Agustina Setia; Anak Agung Ayu Mirah Adi (Kupang Journal of Food and Nutrition Research, 2020)
Background. Child's growth and development are determined by the condition of the fetus in the womb and the nutritional intake of the mother during pregnancy. Mothers with less food intake during pregnancy will experience growth disorders and Low Birth Weight (LBW). Purpose. The purpose of this research is to analyze the relationship between omega-3 fatty acid intake, nutritional status of third trimester pregnant women and the incidence of low birth weight in Ende Regency, East Nusa Tenggara (NTT) Province. Method. This type of research is an observational analytic research with a cohort approach. This research was conducted from January to March 2019. Samples were selected by purposive sampling of 109 research subjects. The data were collected using the SQ-FFQ questionnaire and Form Recall and analyzed using the chi-square test with a degree of confidence of 95% (α = 0.05). Result. There is a relationship between omega-3 fatty acid intake and low birth weight (p = 0.045; RR = 2.060; 95% CI 0.970 - 4.373) and there is a relationship between nutritional status of the third trimester pregnant women and low birth weight (p = 0,000; RR = .17,931; 95% CI 6,844 - 46,978). Conclusion. Pregnant women with deficient omega-3 fatty acids intake are 2 times more likely to give birth to low birth weight babies. Pregnant women with CED are 17.9 times more likely to give birth to babies with low birth weight. Keywords: omega-3, nutritional status, LBW